1991
DOI: 10.1111/j.1476-5381.1991.tb12295.x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of capsaicin‐sensitive nerves in the bronchomotor effects of arachidonic acid and melittin: a possible role for lipoxin A4

Abstract: 1 Functional studies have been performed to evaluate the potential involvement of capsaicin-sensitive nerves in the bronchomotor responses evoked by lipid mediators produced from the metabolic breakdown of arachidonic acid (AA) in the guinea-pig bronchus. 2 In the presence of indomethacin, the exogenous administration of AA (0.01-1 mM) produced a concentration-dependent contractile response in guinea-pig isolated bronchial rings. AA-induced contractions were augmented by epithelium-removal and by thiorphan (10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1994
1994
2005
2005

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…We and others have previously shown that a variety of bronchoactive mediators release tachykinins from guinea pig lungs (39)(40)(41)(42). Therefore, the loss of NEP activity observed in antigen-exposed lungs could result in an enhanced response to tachykinins released by other bronchoactive mediators.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have previously shown that a variety of bronchoactive mediators release tachykinins from guinea pig lungs (39)(40)(41)(42). Therefore, the loss of NEP activity observed in antigen-exposed lungs could result in an enhanced response to tachykinins released by other bronchoactive mediators.…”
Section: Discussionmentioning
confidence: 99%
“…Capsaicin desensitization abolished subsequent motor responses to capsaicin itself or stimulation of NANC nerves, while it left unaffected cholinergic responses. Endogenously generated LXA 4 are hypothesized to act partially through the activation of capsaicin‐sensitive sensory nerve fibers (115) and explain the excitatory effects of AA on capsaicin‐sensitive sensory nerves (116). Other studies on isolated human bronchi showed afterwards that capsaicin might exert a contractile (117), relaxant (118) or biphasic action (119) as a function of capsaicin concentration.…”
Section: Lipoxin Effects In Asthmamentioning
confidence: 99%
“…These compounds include 12‐ and 15‐hydroperoxyeicosatetraenoic acids (HPETE) and 5‐ and 15‐hydroxyeicosatetraenoic acids (HETE) and leukotriene B 4 . It has also been shown that lipoxygenase products, including lipoxin A 4 , may be mediators of the excitatory effects of arachidonic acid on capsaicin‐sensitive sensory nerves in the guinea‐pig bronchus (Manzini & Meini, 1991). These effects were only observed in the presence of the cyclo‐oxygenase inhibitor, indomethacin.…”
Section: Introductionmentioning
confidence: 99%